2008
DOI: 10.1182/blood-2007-05-091728
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived CD154 enables T-cell priming and protection against Listeria monocytogenes challenge

Abstract: Collagen exposure in tissue activates platelets, initiates wound healing, and modulates adaptive immunity. In this report, data are presented to demonstrate a requirement for platelet-derived CD154 for both collagen-induced augmentation of T-cell immunity and induction of protective immunity to Listeria challenge. Specifically, we demonstrate that Ad5 encoding the membrane-bound form of ovalbumin (Ad5-mOVA) delivered in collagen induces higher ovalbumin-specific cytotoxic T lymphocyte (CTL) activity in a dose-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(60 citation statements)
references
References 49 publications
1
59
0
Order By: Relevance
“…106 Platelet CD40L augments T-cell immunity to viral challenge and is necessary for optimal production of immunoglobulin G by inducing DC maturation and B-cell isotype switching. 107,108 It has also been suggested that when antigen-specific B and T cells are rare, platelets enhance signals needed for adaptive humoral immunity and germinal center formation. 108 We have recently discovered in a mouse cardiac transplant model that platelets have a central role in maintaining CD4…”
Section: Platelets and Acquired Immune Responsesmentioning
confidence: 99%
“…106 Platelet CD40L augments T-cell immunity to viral challenge and is necessary for optimal production of immunoglobulin G by inducing DC maturation and B-cell isotype switching. 107,108 It has also been suggested that when antigen-specific B and T cells are rare, platelets enhance signals needed for adaptive humoral immunity and germinal center formation. 108 We have recently discovered in a mouse cardiac transplant model that platelets have a central role in maintaining CD4…”
Section: Platelets and Acquired Immune Responsesmentioning
confidence: 99%
“…Indeed, CD40L + WT platelets adoptively transferred to CD40LΚΟ mice activate the protective immune response in virus-or bacteria-infected mice [22][23][24] . However, neither high dose aspirin nor platelet depletion starting at day -1PI affected the primary parasitemia.…”
Section: If Platelets Killed Pf-irbcs Within Rosettes Then Elevated mentioning
confidence: 99%
“…Platelet-derived CD40L also was shown to enhance CD8 + T cell responses and to promote T cell responses postinfection with Listeria monocytogenes (49,50), thereby bridging the gap between innate and adaptive immunity. Such studies extend platelet function to modulation of innate and adaptive immunity through, for example, release of chemokines, cytokines, and immunomodulatory ligands, including CD40L, and showed that platelets, via CD40L, can induce DC maturation (51).…”
Section: Platelet Cd40l (Cd154)mentioning
confidence: 99%